Potential use of cane sugar processing wastewater for tilapia culture - Casalmir, Candelaria Miravite (1980, 1980)
The physico-chemical and biological characteristics of wastewater from a sugar factory in relation to fish culture were assesses. The potential use of cane sugar wastewater for the culture of Tilapia mossambica was investigated. The utilization of Tilapia mossambica, a herbivorous filter feeding specie in the improvement of water quality and the use od cane sugar wastewater in increasing the fish yield were evaluated. The experimental design consisted of exposing thirty test animals to four levels of cane sugar wastewater, i.e., 25% wastewater, 38% wastewater, pretreated wastewater and recirculated cooling water.two runs were conducted with two replications at each level. Tilapia mossambica, reared for 15 days and 1.5 ton fiberglass tanks had a growth rate of as high as 294% in cane sugar wastewater. Experimental species responded best to 25% cane sugar wastewater. The average growth rate of Tilapia mossambica cultured in 25% and 38% wastewater were 223% and 162% respectively, while lower growth rates of 149% and 61% were noted in pretreated wastewater and recirculated cooling water, respectively. Average survival rates of Tilapia mossambica in 25% wastewater was 90%. A decreasing order of 88%, 77% and 21% were noted in 38% wastewater, pretreated wastewater and recirculated cooling water respectively.
The wastewater treatment capacity of the system was indicated by the biochemical oxygen demand removals ranging from 23% to 63% Ammonia-nitrogen removals ranged from 32% to 98% while phosphorous removals varied from 52% to 80%. Based upon the total biochemical oxygen demand load per day, an aquaculture fishpond/stabilization pond system was designed for treating the wastewater from the Central-Santos-Lopez Mill Co., Inc. The proposed system shall consist basically of three (3) anaerobic ponds to reduce the BOD load from 118.5 kg/day to 48 kg/day. The anaerobic pond effluent shall be led to a series of eight (8) aerobic ponds where fish culture/wastewater treatment operations are integrated.
Mimeographed.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman.
Keywords: Sugar-cane as feed; Tilapia